Mycoflora and aflatoxin/fumonisin production by fungal isolates from freshly harvested corn hybrids - Almeida,Adriana P. (2000)
The mycoflora of 3 hybrids of freshly harvested corn grains collected from three regions of the state of São Paulo, Brazil (Assis, Capão Bonito and Ribeirão Preto) was investigated. A total of 66 samples were analyzed focusing on the influence of abiotic factors (moisture content, water activity, temperature and rainfall) on both the prevalence of Aspergillus flavus and Fusarium moniliforme, and the ability of these genera isolates to produce aflatoxins and fumonisins, respectively. In the three surveyed regions, the fungal population comprised mainly Fusarium spp., Penicillium spp., Aspergillus spp. and 2 others filamentous fungal genera, which were isolated from corn kernels showing water activity of 0.30 to 0.99 and moisture content of 5.0% to 20.2%. Among the genera Fusarium and Aspergillus, the most frequent species were F. moniliforme and A. flavus, respectively. Concerning the toxigenic potential of F. moniliforme, all isolated strains (40) produced fumonisins at 20 mug/g to 2168 mug/g (FB1) and/or 10 mug/g to 380 mug/g (FB2). From the 10 A. flavus isolates, 6 strains (60.0%) produced aflatoxins at 615 mug/kg to 30.750 mug/kg (AFB1) and/or 11 mug/kg to 22 mug/kg (AFB2).